Implementasi Program Perlindungan Khusus Anak Dalam Menurunkan Angka Pernikahan Dini Oleh Dp3apm Di Kota Tanjungpinang Tahun 2024 - Desma Tri Anggriani; Novi Winarti; Uly Sophia (CV. ITTC INDONESIA, 2026)
Early marriage remains a social issue in Tanjungpinang City that negatively affects children's education, health, and quality of life. Although the Child Special Protection Program has been implemented by the Department of Women's Empowerment, Child Protection, and Community Empowerment (DP3APM), early marriage rates continue to fluctuate, indicating the need to evaluate the program's implementation. This study aims to analyze the implementation of the Child Special Protection Program in reducing early marriage rates and to identify the factors influencing its implementation. The research employed a descriptive qualitative method using the policy implementation theory of Van Meter and Van Horn, which includes policy standards and objectives, resources, inter-organizational communication, characteristics of implementing agencies, implementers' attitudes, and social, economic, and political environments. Data were collected through interviews and documentation. The findings indicate that the program has not been implemented optimally due to the absence of specific technical guidelines, limited human and financial resources, and unsustained inter-agency coordination. Although the implementing agencies have performed their roles effectively and demonstrated strong commitment, limited public awareness of early marriage and family economic conditions that reduce parental supervision remain significant contributing factors. Therefore, strengthening regulations, enhancing resources, and improving cross-sectoral coordination are essential to increase the effectiveness of the Child Special Protection Program in reducing early marriage rates in Tanjungpinang City.